Raw Life, New Hope Decency, Housing and Everyday Life in a Post-Apartheid Community - Ross, Fiona (UCT Press, 2009)
The Cape Flats, a windswept, barren and sandy area which rings Cape Town, is home to more than a million people. Many live here in sprawling shack settlements. The post-apartheid state is attempting to eradicate such settlements by providing formal houses in planned residential estates. Raw Life, New Hope is a longitudinal study of the residents of one such shack settlement, The Park, who moved to new, 'formal' houses in The Village, at the turn of the millennium. It introduces readers to core social science topics and modes of theorising. Over 17 years the author has traced how ordinary people attempt to live in accord with their ideals of decency under almost impossible circumstances, and the effects of material changes in their lives after 1994, including the provision of housing. Photos, maps, anecdotes, recipes and philosophical reflections on subjects that arose during conversations elicit a sense of the everyday and of how people try to solve the problems of poverty.